The thiamine deficiency syndrome M74, a reproductive disorder of Atlantic salmon (Salmo salar) feeding in the Baltic Sea, is related to the fat and thiamine content of prey fish - Keinänen, Marja; Uddström, Annika; Mikkonen, Jaakko; Casini, Michele; Pönni, Jukka; Myllylä, Timo; Aro, Eero; Vuorinen, Pekka J. (ICES Journal of Marine Science, 2012)
Abstract Keinänen, M., Uddström, A., Mikkonen, J., Casini, M., Pönni, J., Myllylä, T., Aro, E., and Vuorinen, P. J. 2012. The thiamine deficiency syndrome M74, a reproductive disorder of Atlantic salmon (Salmo salar) feeding in the Baltic Sea, is related to the fat and thiamine content of prey fish. – ICES Journal of Marine Science, 69: 516–528. This study clarifies how the diet of Baltic salmon leads to thiamine deficiency in eggs, and consequently to M74 mortality of yolk-sac fry. The main prey species, sprat (Sprattus sprattus) and herring (Clupea harengus membras), and their biomass in the Baltic Proper (BPr) and the Bothnian Sea, the two feeding grounds of salmon originating from the northern Gulf of Bothnia rivers, are compared. The thiamine concentration of both prey species is lowest in the youngest age groups. Because average fat content and energy density are greater in sprat than in herring, and greatest in youngest sprat, the supply of thiamine per unit energy is least in a diet containing many young sprat. Also, the greater is the supply of thiamine and fat from sprat in the southern BPr in the preceding year, the lower the concentration of thiamine in salmon eggs. Thiamine deficiency in eggs results from an unbalanced diet abundant in fatty prey fish, such as young sprat, from which the supply of thiamine is insufficient in proportion to the supply of energy and unsaturated fatty acids for salmon, which must undergo a long prespawning fasting period.